Japanese Encephalitis in a Renal Transplant Recipient - Vaishnavi Venkatasubramanian; Sahil Garg; Ishani Bora; Jasmine Sethi (Indian Journal of Kidney Diseases)
Infectious complications are a common cause of neurological abnormality in the postrenal transplant setting, often leading to considerable morbidity and mortality. This is the first published report of Japanese encephalitis in a renal transplant recipient. It is particularly relevant for low- and middle-income countries like ours. Timely imaging and lumbar puncture examination in a renal transplant recipient presenting with altered sensorium is crucial for early diagnosis and treatment.